Dyeing of Wool Fibers with Natural Fungal Dye from Suillus luteus - Kasikara Pazarlioglu, Nurdan; Akkaya, Alper; Merih Sariisik, A.; Erkan, Gokhan; Perrin Akcakoca Kumbasar, E. (Asian Journal of Chemistry, 2011)
Suillus luteus is a pored, edible mushroom of the genus Suillus in the Suillaceae family in Boletales order. The wool fabrics were dyed with the ethanolic extract of S. luteus fruit bodies at different pH values with various mordants. The greatest colour yield was obtained at pH 3 without mordant. Highest K/S values were obtained at pH 5 and 6 mordanting with copper sulfate. However at pH 4, 3 and 2 the highest K/S values were obtained mordanting with tin(II) chloride. Although, all dyed samples have good washing and crocking fastness, poor washing fastness colour change values were observed at pH 2 and 3 without mordanting.